Sodium Lignin Sulfonate (SLS) and Pomegranate Rind Extracts (PRE) Bio-macro-molecule: A Novel Composition for Making Fire Resistant Cellulose Polymer. Issue 15 (18th November 2022) - Basak, S.; Ali, S. Wazed
ABSTRACT: A novel formulation of the sodium lignin sulfonate (SLS) [bio based branched chain lignin polymer modified with the sulfonic acid] and the pomegranate rind extract (PRE), a wastage plant biomolecule, has been applied to the cellulosic cotton fabric to make it flame retardant. It was found that the control, 10% SLS and the PRE treated cotton fabric showed the limiting oxygen index (LOI) value of 18, 25, and 24, respectively and completely burnt within one to two minutes in the vertical flammability test. On the contrary, (PRE+ 10% SLS) treated cotton fabric showed 32% add-on and the LOI value of 32 with the specific char length of 40 mm after the completion of the vertical flammability test as per IS1871 method A. Extent of the afterglow duration and the char length, both have been decreased with increasing the percentage concentration of the SLS [5 to 10% (W/V)] into the PRE mixture. Thermo-gravimetry (TG) analysis of the control, PRE and the 10% SLS treated cotton fabric showed only 10% remaining char mass at 450°C in air atmosphere whereas the (PRE+ 10% SLS) treated fabric showed much lower mass loss rate and 45% remaining char mass at the said temperature. Moreover, the char morphology of the (PRE+ 10% SLS) formulation treated fabric showed structural integrity (weave of the fabric) with the presence of the small bubbles after the completion of the combustion phenomena. Mechanism of the fire retardancy revealed the fact that during the treatment, nitrogen containing alkaloids, long chain carbon molecule, poly phenolic compounds (present in the PRE) and the sulfur containing sulfonate groups, polyphenolic compounds (present in the SLS) deposited on the cotton fabric surface, combinedly acted on the flame retardancy (to arrest the both flame and the afterglow) and the char formation of the underlying cellulose structure, during burning. Moreover, the detail color values of the control and the treated fabrics also have been elucidated in the present research context.